Synthesis and use of 6, 6, 6-trifluoro-L-fucose to block core-fucosylation in hybridoma cell lines. (30th July 2018) - McKenzie, Nicole C.; Scott, Nichollas E.; John, Alan; White, Jonathan M.; Goddard-Borger, Ethan D.
Abstract: Many monoclonal antibodies (mAbs) used in cancer immunotherapy mediate tumour cell lysis by recruiting natural killer (NK) cells; a phenomenon known as antibody-dependent cellular cytotoxicity (ADCC). Eliminating core-fucose from the N -glycans of a mAb enhances its capacity to induce ADCC. As such, inhibitors of fucosylation are highly desirable for the production of mAbs for research and therapeutic use. Herein, we describe a simple synthesis of 6, 6, 6-trifluoro-l -fucose (F3Fuc), a metabolic inhibitor of fucosylation, and demonstrate the utility of this molecule in the production of low-fucose mAbs from murine hybridoma cell lines. Graphical abstract: Image 1 Highlights: 6, 6, 6-Trifluoro-l -fucose (F3Fuc) can be readily synthesised from d -mannose. F3Fuc is effective at blocking antibody fucosylation in hybridoma cell lines. F3Fuc is superior to other fucose mimics at blocking fucosylation in hybridoma cell lines.